2008
DOI: 10.1007/s12031-008-9044-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cell Cycle Inhibitors on Tau Phosphorylation in N2aTau3R Cells

Abstract: Neurofibrillary tangles are one of the pathologic hallmarks of Alzheimer's disease (AD). They are composed of paired helical filaments (PHF) containing hyperphosphorylated forms of tau. Hyperphosphorylation of certain tau sites favors its dissociation from the microtubules (MT), interfering with axonal transport and compromising the function and viability of neurons. Reappearance of cell cycle proteins have been reported in neurons exhibiting tau aggregation, suggesting that an aberrant cell cycle occurs befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Importantly, a number of identified molecules have known connections to A␤ neurotoxicity. For example, previous work showed that cyclophosphamide, a DNA cross-linking agent and a hit in our screen, decreased tau phosphorylation at Ser-396/ 404 site (17). This result is consistent with the notion that aberrant neuronal cell cycle re-entry may lead to tau hyperphosphorylation, and thus inhibiting cell cycle progression may be one target of therapeutic intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, a number of identified molecules have known connections to A␤ neurotoxicity. For example, previous work showed that cyclophosphamide, a DNA cross-linking agent and a hit in our screen, decreased tau phosphorylation at Ser-396/ 404 site (17). This result is consistent with the notion that aberrant neuronal cell cycle re-entry may lead to tau hyperphosphorylation, and thus inhibiting cell cycle progression may be one target of therapeutic intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Among these are the increased tau phosphorylation and microtubular destabilization that accompanies mitosis [28] and the dose dependent effects of CCL inhibitors on tau phosphorylation [29]. Aβpeptides also influence CCL re-entry, chromosome missegregation and aneuploidy, and induce abnormal cytoplasmic translocation of CDK5 to the nucleus [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…G2/M blockers (paclitaxel, vinblastine, and vincristine) have a dose‐dependent effect on tau phosphorylation at Ser‐202 and Ser‐396/404 in N2aTau3R cells. The Ser‐201 and Ser‐396/404 phosphorylation on tau are associated with neurofibrillary tangles (Conejero‐Goldberg, Townsend, & Davies, ). During mitosis, c‐Jun N‐terminal kinase phosphorylates R406W tau (Tatebayashi et al, ).…”
Section: The “Amyloid‐beta Accumulation Cycle”mentioning
confidence: 99%